Association between family support and activities of daily living among patients undergoing hemodialysis: A cross-sectional study - Intan Kumala Sari; Dwi Soelistyoningsih; Achmad Rifa'i; Abdul Qodir (Lentera Perawat, 2026)
Background: Patients with hemodialysis frequently experience physical limitations that may affect their capacity to accomplish Activities of Daily Living (ADL). This decline in independence increases patients’ dependence on others. Family support plays a crucial role in helping patients maintain independence and refine the quality of their lives during long-term treatment. Objective: This study aimed to determine the association between family support and Activities of Daily Living (ADL) among patients undergoing hemodialysis. Methods: A cross-sectional analytical correlational study was implemented at Muhammadiyah General Hospital. The participants were 50 patients with chronic kidney disease undergoing hemodialysis for at least three months, aged 18-60 years, selected through purposive sampling. Family support was assessed using the Perceived Social Support–Family (PSS-FA) instrument, while independence in activities of daily living (ADL) was measured using the Barthel Index. Descriptive statistics were used to summarize participants characteristics. The relationship between family support and ADL was analyzed using Somers' d test at the 5% significance level. Results: The evidence indicates that most respondents received high levels of family support (86%) and had relatively good levels of independence in performing ADL (68%). Statistical analysis indicated a critical association between family support and ADL among hemodialysis patients (p=0.001; r = 0.61). These findings imply that higher levels of family support contribute to improve patient independence in carrying out daily activities. Conclusion: Family support is significantly associated with the capacity of hemodialysis patients to perform Activities of Daily Living. Strengthening family involvement through family-centered nursing interventios may help improve patient independence and overall well-being during long-term hemodialysis treatment.